Potentialities of using PCM in residential buildings in Portugal - Mustaparta, Olli (2013)
In the past few years the energy crisis has been a big topic around the world and many studies have been made to improve the efficiency of energy use. One of the research areas is the building sector and his heating and cooling systems. Constantly changing weather has a large effect on room temperatures and thermal comfort of residents. Controlling devices and appliances are consuming a large amount of energy to keep the temperature within the comfort range. This work reviews the Phase Change Materials (PCM) use in new and refurbished buildings to decrease the energy consumption. PCMs can be used in different structures like roofs, walls and floors and by correct placement the maximum potential may be achieved. The main objective is to stabilize the temperature fluctuations inside and reduce the energy use of heating and cooling systems. This study takes in consideration also the financial matters and additionally there is a short review of the possible application of PCM in northern countries.